At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I'll try to help. Are you still around?
Okay, gimme a sec. (writing problems down)
The first trick, is to line the equations up, with all of the variables and numbers in columns. This makes it easier to see what we're looking at.
Yeah I did that. I need to write it in standard form, but the x and y are in the different places.
So, in other words, here is how I rewrote them. -y + 1.2x = 32.2 y - 5x = 13
Oh, lol, I didn't even think about standard form.
The original equation for the first one is 2x - y = 32
How did you get 1.2x?
Ahhhh! Okay. Let's rewrite the equations in standard form. ( I read your first post wrong)
2x - y = 32 5x - y = 13
Do you remember the additive identity property?
Okay. That property lets us move the addition/subtraction terms around however we like.
That's how I was able to rearrange the terms
Do you also remember that you can multiply both sides by a negative?
I know that part to.
So did you arrange the like terms correctly?
2x - y = 32 5x - y = 13 ?
I'm going to multiply the top equation by negative one, and then I'm going to add the two equations together. And, yes.
That's what I see.
Standard form is X + Y = Z
Your going to solve for one variable right?
Yup. One way we can accomplish this is by adding the two equations together.
I thought standad form was Ax + By = c?
Uhh.. Yes. You're more right. (Sorry, haven't used standard form in a while)
Okay. So let's multiply by (-1) 2x - y = 32 becomes -2x + y = -32
Okay and then your going to add it?
I got 3x = - 19
Yes! Now, it becomes very apparent why adding equations is awesome. -2x + y = - 32 + 5x - y = 13 ( I need to double check the negatives)
Yeah, it's -2x + y = -32 + 5x - y = -13 I didn't need to multiply the top equation by negative one, (oops!), so I multiplied the bottom one, so that they'll add up nicely again. (Sorry for the confusion)
Would you add them together please?
3x = - 45
x = -15
Yup! Now you just need to clean up.
Now, substitute x for - 15 on another equation, and you'll get y. ^^
-2(-15) + y = -32 30 + y = -32 y = -2
Hmm..... Something went wrong. Argh! Sorry!!
I use it in the original equation don't I?
Alright, let's try this one more time! Hang on, gimme a second.
2(-15) - y = 32 -30 - y = 32 -y = 62 y = -62
Hey I checked..and your right.
The solution is (-15, -62)
O_O Yeah. I checked it. Just some bad 'rithmatic
Ow. Okay, cool. Whew. I was worried I led you down the wrong path. Hehe
Anyway, awesome. Take it easy, and God bless with the rest of your homework. ... Yikes. I think I need some sleep!
Lol. Me too.